Subjektifitas dan Hegemoni Pemimpin Sufi: Kritik Atas Pandangan Syeikh Akbar Fathurahman Terkait Moderasi Beragama - Nawwaf, Aufa Varrassyah (Spiritualita, 2025)
The Spirit of religious moderation has been embodied in Indonesian society for a long time, and Sufis played a significant role in disseminating religious moderation or wasaṭiyya. However, wasaṭiyya only acquired serious attention from the Indonesian government in 2016. It marked the beginning of wasaṭiyya as the national project. Thus, this study aims to analyze the wasaṭiyya thoughts of a Sufi figure who emerged to prominence after 2016. The focus of this study is examining the notion of Syekh Akbar Fathurahman, the current murshid of Tariqa Idrisiyyah who actively engages in social media to spread and propagate his teaching. This study is qualitative research and employs the critical theory paradigm by Jurgen Habermas. The primary source is a YouTube video that presented Syekh Fathurahman’s lecture on religious moderation. The findings indicate that there was ideological indoctrination that led to distorting the discourse of religious moderation by reducing its concept. Syekh Fahurahman tended to direct its discourse to the Sufism aspect to support the interest of tariqa. In addition, he narrowed its wide concept by linking it to certain groups that meet several criteria. It causes the elimination of many parties that do not align with the proposed parameter. By doing so, Syekh Fathurahman aimed to establish the hegemony. Nevertheless, apart from the distortion, Syekh Fathurahman also presented the ideal meaning of religious moderation, showing that he is not an extreme Sufi. Additionally, this study also finds that there is a paradox and ambiguity in the connection between fiqh, taṣawwuf, and moderation.